Analisis Persepsi Masyarakat Tentang Dampak Limpasan Air Permukaan Pada Lingkungan Permukiman Di Loa Buah, Kota Samarinda - Patricia Yoanita Effendi; Junita Nur Aulia; Dina Hayati Putri; Nova Hariani (Yayasan Ekologi Masyarakat dan Sains, 2026)
Surface water runoff in residential areas can lead to flooding, water pollution, and infrastructure damage. This study aims to analyze community perceptions of the impact of surface runoff in Loa Buah, Samarinda City. The method used is descriptive qualitative, involving interviews with purposively selected respondents. The results show that residents are aware of the increased water volume during rain, which causes puddles, carries sediment, and pollutes clean water sources. The perceived impacts include road damage, health issues, and economic burdens. The community expects a permanent solution from the government through improved drainage systems and well-managed spatial planning.